Confronting Subtle Sexism in An Indonesian EFL Textbook - Ana Humardhiana; Yayah Nurhidayah (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
Language is a powerful tool to communicate ideologies and build a society. Through language, we can see what kind of society we are living in; and apparently, we are living in a society where sexism flourishes without us realizing it. This type of sexism is called as subtle sexism, appearing to be unintentional and harmless because the unequal and unfair treatmeant of women is perceived to be normative. In Indonesia, subtle sexism can be found in EFL textbooks. As the main language input, textbooks can transfer cultural values and ideologies through the targeted language. Hence, subtle sexism is ‘softly’ hidden on the pages and readers – students in this case – are not aware that they are being indoctrinated. This study examined an Indonesian EFL textbook entitled Bahasa Inggris Kelas XII for the twelfth graders in Indonesia which was published by the Ministry of Education and Culture. By implementing content analysis, this research has two objectives, i.e. (1) to find out whether the book promotes subtle sexism, and (2) how teachers, as the last filters, can confront subtle sexism in the book and other EFL textbooks in general. The results show that even though the textbook does not reflect any signs of blatant and covert sexism, it still promotes subtle sexism that the writers might not aware of. Also, this study tries to propose some suggestions for teachers to confront subtle sexism in EFL textbooks, such as using a gender bias checklist, making changes or creating new original materials, fostering a critical class discussion by using the sexist textbooks, and teaching gender-fair language.